Transcriptomic Analysis of Two Thioalkalivibrio Species Under Arsenite Stress Revealed a Potential Candidate Gene for an Alternative Arsenite Oxidation Pathway - Ahn, Anne-Catherine; Cavalca, Lucia; Colombo, Milena; Schuurmans, J. Merijn; Sorokin, Dimitry Y.; Muyzer, Gerard (Frontiers in Microbiology, 2019)
The genus Thioalkalivibrio includes haloalkaliphilic chemolithoautotrophic sulfur-oxidizing bacteria isolated from various soda lakes worldwide. Some of these lakes possess in addition to their extreme haloalkaline environment also other harsh conditions, to which Thioalkalivibrio needs to adapt. An example is arsenic in soda lakes in eastern California, which is found there in concentrations up to 3000 µM. Arsenic is a widespread element that can be an environmental issue, as it is highly toxic to most organisms. However, resistance mechanisms in the form of detoxification are widespread and some prokaryotes can even use arsenic as an energy source. We first screened the genomes of 76 Thioalkalivibrio strains for the presence of known arsenic oxidoreductases and found 15 putative ArxA (arsenite oxidase) and two putative ArrA (arsenate reductase). Subsequently, we studied the resistance to arsenite in detail in Tv. jannaschii ALM2T and Tv. thiocyanoxidans ARh2T by comparative genomics and by growing them at different arsenite concentrations followed by arsenic species and transcriptomic analysis. Tv. jannaschii ALM2T, which has been isolated from Mono Lake, an arsenic-rich soda lake, could resist up to 5 mM arsenite, whereas Tv. thiocyanoxidans ARh2T, which was isolated from a Kenyan soda lake, could only grow up to 0.1 mM arsenite. Interestingly, both species oxidized arsenite to arsenate under aerobic conditions, although Tv. thiocyanoxidans ARh2T does not contain any known arsenite oxidase, and in Tv. jannaschii ALM2T, only arxB2 was clearly upregulated. However, we found the expression of a SoeABC-like gene, which we assume might have been involved in arsenite oxidation. Other arsenite stress responses for both strains were the upregulation of the vitamin B12 synthesis pathway, which can be linked to antioxidant activity, and the up- and downregulation of different DsrE/F-like genes whose roles are still unclear. Moreover, Tv. jannaschii ALM2T induced the ars gene operon and the Pst system, and Tv. thiocyanoxidans ARh2T upregulated the sox and apr genes as well as different heat shock proteins. Our findings for Thioalkalivibrio confirm previously observed adaptations to arsenic, but also provide new insights into the arsenic stress response and the connection between the arsenic and the sulfur cycle.